Mining landscape, alternative economy and heritagisation: A theoretical perspective - Payel Ghosh; Srabani Sanyal (National Geographical Journal of India, 2022)
Mines and their influential area are widespread and so are the associated problems like resource depletion, environmental degradation, economic instability, etc. The sufferings intensify even more after the mine closures. This exercise brings heritagisation as a panacea to protect the mining landscape against its adverse effects. Assignment of heritage tags to the mining assets is a new trend to repurpose them as tourist attractions and bring forth mining heritage tourism as an alternative economy. This theoretical work is based on the review of previously published literature and secondary data. The objectives are to establish a link between mining and heritage and identify the process of heritagisation of the mining landscape. A bibliographic survey is conducted to highlight the association between mining entities and natural and cultural heritage properties. With the help of some economic models, the role of heritagisation as an alternative to the conventional economy i.e., mining, is justified. A three-stage model of the heritagisation process is prepared as an outcome of the study that shows how a successful repurposing of mines is possible through the sectoral transformation from mineral production to heritage tourism, which in turn also serves as a tool for sustainable development.